The effect of vertical air gaps to thermal transmittance of horizontal thermal insulating layer - Šadauskienė, Jolanta; Buska, Andrius; Burlingis, Arūnas; Bliūdžius, Raimondas; Gailius, Albinas (Journal of Civil Engineering and Management, 2009)
In order to reduce the amounts of work at the construction site, single‐ply dual density thermal insulating roofing boards are used with increasing frequency for thermal insulation of flat roofs. In this case, the joints between boards are not overlapped by the other ply over it; therefore gaps of varying width form between the sides of the boards through the entire thickness of the insulating layer, whose effect on the effective thermal conductivity of the thermal insulating layer must be evaluated. The aim of this project was to assess the reliability of standard method, used to determine the impact of such air gaps on the effective thermal conductivity of the thermal insulating layer by comparing the results of calculations and the results of measurements of thermal conductivity, also to determine the correction factors for thermal transmittance of horizontal thermal insulation layers due to the forming vertical air gaps between the single‐ply mineral wool boards. After measurements of thermal resistances of 50 mm thick thermal insulation board with the air gaps which width varied from 3 mm to 20 mm, it was determined that the thermal conductivity value of the air gaps increases with the increment of the width of air gaps. After completion the experimental measurements of thermal conductivity it was determined that the height of closed and unventilated or partly ventilated air gaps has no effect on the properties of effective thermal conductivity of the thermal insulation layer when the air gap width is up to 5 mm. When wider unventilated or partly ventilated air gaps occur, the effective thermal conductivity coefficient increases proportionally as the height of the air gaps increases. Calculated according to the standard method the affix to the thermal transmittance is overly general and not always appropriate. In some cases it is 6 times higher or 4 times lower than the measured one. In this paper a method to evaluate the effects of air gaps by the use of correction factor to the thermal transmittance of the horizontal thermal insulating layer is proposed. Santrauka Nornt sumažinti darbų apimtis statybos vietoje, stogams šiltinti vis dažniau naudojamos vienu sluoksniu klojamos dvitankės termoizoliacinės plokštės. Šiuo atveju plokščių sandūros neperdengiamos, todėl tarp plokščių kraštinių susidaro įvairaus pločio plyšių, kurių įtaka termoizoliacinio sluoksnio šilumai perduoti turi būti įvertinta. Šio darbo tikslas yra įvertinti standartinio metodo, taikomo tokių plyšių poveikiui sluoksnio šilumos laidumui, patikimumui nustatyti lyginant skaičiavimo ir šilumos laidumo matavimų rezultatus, nustatyti horizontaliojo termoizoliacinio sluoksnio šilumos perdavimo koeficiento pataisas dėl vertikaliųjų oro plyšių susidarymo. Apskaičiavus 50 mm storio termoizoliacinio sluoksnio oro plyšių šilumines varžas, kai plyšių plotis yra nuo 3–20 mm, nustatyta, kad oro plyšių šilumos laidumo koeficiento vertė didėja didėjant oro plyšio pločiui. Atlikus eksperimentinius šilumos laidumo matavimus, nustatyta, kad susidarančių uždarų ir nevėdinamų arba iš dalies vėdinamų oro plyšių aukštis neturi įtakos termoizoliacinio sluoksnio šilumos laidumo savybėms, kai oro plyšys yra iki 5 mm pločio. Esant platesniems uždariems ir nevėdinamiems oro plyšiams, šilumos laidumo koeficientas proporcingai didėja didėjant oro plyšių aukščiui. Pagal standartinį metodą skaičiuotas šilumos perdavimo koeficiento priedas yra per daug apibendrinantis ir ne visada tinkamas. Kai kuriais atvejais jis yra 6 kartus didesnis arba 4 kartus mažesnis už išmatuotąjį. Šiame darbe pasiūlytas horizontaliojo termoizoliacinio sluoksnio šilumos perdavimo koeficiento priedo, naudojamo plyšių įtakai įvertinti, skaičiavimo metodas. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: oro plyšys, dvitankė termoizoliacinė plokštė, šilumos laidumas, šilumos perdavimo koeficientas.